MtDNA profile of West Africa Guineans: towards a better understanding of the Senegambia region - Rosa, Alexandra (2020)
The matrilineal genetic composition of 372 samples from the Republic of Guiné-Bissau (West African coast) was studied using RFLPs and partial sequencing of the mtDNA control and coding region. The majority of the mtDNA lineages of Guineans (94%) belong to West African specific sub-clusters of L0-L3 haplogroups. A new L3 sub-cluster (L3h) that is found in both eastern and western Africa is present at moderately low frequencies in Guinean populations. A non-random distribution of haplogroups U5 in the Fula group, the U6 among the "Brame" linguistic family and M1 in the Balanta-Djola group, suggests a correlation between the genetic and linguistic affiliation of Guinean populations. The presence of M1 in Balanta populations supports the earlier suggestion of their Sudanese origin. Haplogroups U5 and U6, on the other hand, were found to be restricted to populations that are thought to represent the descendants of a southern expansion of Berbers. Particular haplotypes, found almost exclusively in East-African populations, were found in some ethnic groups with an oral tradition claiming Sudanese origin.